Structure characterization and optical properties investigation of the four main components of the classical phenazinium dye Safranin O. Issue 24 (28th October 2019) - Wan, Hong; Chen, Hong; Chu, Yueying; Ju, Xiulian; Jiang, Haipeng
Abstract : The structures of the four main components in classical phenazinium dye safranin O were firstly identified, there was somewhat different in their absorbance properties and remarkably different in their fluorescence properties. Abstract : Safranin O is an important and classical phenazinium dye; since the 19 th century, it has been extensively used in the academic field as a spectroscopic probe and indicator. Surprisingly, we found that this long-used reagent is without exception a mixture. In this study, the four main components in a Safranin O sample were prepared, and their chemical structures were elucidated for the first time. Optical property investigations showed that the components had somewhat different absorbance properties and markedly different fluorescence properties, and their structure–optical activity relationships were also discussed. It could be inferred that the variation of each component in the content would unavoidably result in inconsistent optical data when using this Safranin O reagent as a spectroscopic probe or indicator. Considering the accurate transfer of measurement results between laboratories, high-purity Safranin O is in urgent demand in the academic field.